Rhodium‐Catalyzed Benzylic Addition Reactions of Alkylarenes to Michael Acceptors. (19th July 2022) - Li, Yuntong; Wu, Wen‐Qiang; Zhu, Hui; Kang, Qi‐Kai; Xu, Lun; Shi, Hang
Abstract: The use of alkylarenes as nucleophile precursors in benzylic addition is challenging because the benzylic hydrogen atoms of these compounds are inert to deprotonation. Herein, we report Rh‐catalyzed benzylic addition of alkylarenes to Michael acceptors for the formation of C(sp 3 )−C(sp 3 ) bonds. The catalyst is proposed to activate the aromatic ring via η 6 ‐coordination, dramatically facilitating deprotonation of the unactivated benzylic C−H bond and addition of the resulting carbanion to the α, β‐unsaturated double bond in the absence of bases. Notably, this byproduct‐free method provides an access to all‐carbon quaternary centers through the development of ligands. Abstract : A rhodium catalyzed benzylic C(sp 3 )− C(sp 3 ) bond formation with Michael acceptors was achieved. The catalyst is proposed to activate the aromatic ring via η 6 ‐coordination, dramatically facilitating benzylic deprotonation and addition of the resulting carbanion to the electrophile in the absence of a base. This byproduct‐free method features a wide scope of alkylarenes bearing primary, secondary, or tertiary benzylic C−H bonds.